2018
DOI: 10.1021/acs.iecr.7b03712
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Assisted Mechanochemical Synthesis of Copper Based MOF-505 for the Separation of CO2 over CH4 or N2

Abstract: Mechanochemical synthesis, driven the chemical transformation by mechanical force, has been a rapid and efficient strategy to prepare metal–organic frameworks (MOFs). In this work, a liquid-assisted mechanochemical method has been successfully applied to the synthesis of copper based MOF-505. The crystallinity and porosity of MOF-505 were investigated by adjusting the synthesis parameters, such as added solvent (type and amount) and grinding time. Results showed that the type and amount of added solvent were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 58 publications
1
39
0
Order By: Relevance
“…[ [55][56][57][58][59] Such excellent performance reveals the bright promise of compound 1 for small molecule separation and purification. The aforementioned results were further confirmed by the isosteric heat of adsorption (Q st ) which was calculated via the experimental adsorption data, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ [55][56][57][58][59] Such excellent performance reveals the bright promise of compound 1 for small molecule separation and purification. The aforementioned results were further confirmed by the isosteric heat of adsorption (Q st ) which was calculated via the experimental adsorption data, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MOF-5-B optimized by mechanochemical synthesis showed preferential adsorption for long chain alkanes at low pressure. MOF-505 was synthesized using the mechanochemical technique, and it was confirmed that the type and amount of the added solvent were decisive factors in producing MOF-505 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This fast reaction speed is due to the sufficient energy provided by the mechanical force during ball milling. From a thermodynamic point of view, generally, the chemical potential of a substance in the solid state is higher than that of the same one in the liquid state [30,38,39,40]. Thus, the driving force of the formation of Ni-MOF is higher than that of solution-based synthesis method [30].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, it is even possible to be more rapid and efficient than solvent-based methods. Since the synthesis of the moderately porous copper(II) isonicotinate MOF in pioneering work reported by James’ group [21], milling procedures have been successfully applied for the synthesis of several popular MOF materials, such as zeolitic azolate frameworks [22,23], rare-earth(III) metal−organic frameworks [24], isoreticular metal-organic frameworks (IRMOFs) [25], iron(III) trimesate MIL-100 (MIL = Materials of Institut Lavoisier) [26], MOF-74 [27], Hong Kong University of Science and Technology (HKUST)-1 [28], Cu 2 I 2 (triphenylphosphine) 2 (L) n ( n = 1, 2) [29], copper-based MOF-505 [30], and UiO-66 (UiO = University of Oslo) and UiO-67 derivatives [31,32,33]. Previously, Pichon and James [21] described a survey of the potential reactions between Ni(OAc) 2 , Ni(NO 3 ) 2 , NiSO 4 , and H 3 BTC under mechanochemical solvent-free conditions and, unfortunately, only grinding nickel sulfate with H 3 BTC gave a partial reaction.…”
Section: Introductionmentioning
confidence: 99%